2022
DOI: 10.22578/ijms.20.2.8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Genotypes and Pre-core and Core Genes Mutations in a Sample of Iraqi Patients with Chronic Hepatitis B Infection

Hiba Hussain,
Arwa M. Al-Shuwaikh,
Abbas Ahmed

Abstract: Background: Genomic studies of hepatitis B virus (HBV) diversity are becoming increasingly significant to understand how HBV mutations interact with a wide spectrum of clinical and pathological disorders. Objective: This study focused on identifying HBV genotypes and determining the status of pre-core (PC) and core promoter (CP) mutants. Methods: Nested polymerase chain reaction was used to identify the viral genotypes of 100 patients with chronic HBV infection. Only 30 samples out of 100 were selected to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…The results revealed 21 nucleic acid variants corresponding to five amino acid substitutions (103G>V, 109I>A, 109I>M, 109I>V, and 110S>A) in the core protein's amino acid sequence. Hussain et al (24), in a study in Iraq, identified Pre-Core/Core mutations in 50% of CHB patients, regardless of the HBeAg status, and most of their samples belonged to genotype D. In a study from Iran, Farshadpour et al (25) detected Pre-Core/Core mutations in 11 out of 19 diabetic patients carrying HBV DNA, most of which were also genotype D (subtypes D1 and D3). In terms of more frequent mutations (such as alterations in amino acid residues 109 and 143 in the Pre-Core/Core protein), our findings are similar to those of Farshadpour et al In addition to genotype D, Pre-Core/Core mutations are also found in other HBV genotypes as well (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results revealed 21 nucleic acid variants corresponding to five amino acid substitutions (103G>V, 109I>A, 109I>M, 109I>V, and 110S>A) in the core protein's amino acid sequence. Hussain et al (24), in a study in Iraq, identified Pre-Core/Core mutations in 50% of CHB patients, regardless of the HBeAg status, and most of their samples belonged to genotype D. In a study from Iran, Farshadpour et al (25) detected Pre-Core/Core mutations in 11 out of 19 diabetic patients carrying HBV DNA, most of which were also genotype D (subtypes D1 and D3). In terms of more frequent mutations (such as alterations in amino acid residues 109 and 143 in the Pre-Core/Core protein), our findings are similar to those of Farshadpour et al In addition to genotype D, Pre-Core/Core mutations are also found in other HBV genotypes as well (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the sequences of the C gene-based G genotype have been less frequently deposited in the NCBI database. It appears that genotype D is the main HBV genotype in Iraq (24,25,31). There are some reports suggesting a role for HBV genotype in HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…Databases of HBV sequences such as NCBI virus and Hepatitis B virus (HBV) databases frequently consist of whole genome sequences of individual viral isolates obtained from Sanger sequencing. In Iraq, studies were conducted to determine the viral genotypes using molecular techniques of different genes or regions of HBV genomes [ 9 , 10 ]. Nonetheless, there are no reports on the whole genome sequence of HBV isolated from Iraqi patients.…”
Section: Introductionmentioning
confidence: 99%